Transitioning to a Cashless Economy: Drivers and Inhibitors of Electronic Payment System Adoption among Micro, Small, and Medium Enterprises - Jayson Diaz (International Journal of Management, Knowledge and Learning)
Purpose: This study investigates the adoption of electronic payment systems among Micro, Small, and Medium Enterprises (MSMEs) in Koronadal City, focusing on identifying the drivers and inhibitors influencing this shift toward a cashless economy.